UJI COBA PEMANFAATAN KAMUS BAHASA JEPANG PARIWISATA GUNA MENINGKATKAN PEMAHAMAN KOSAKATA BAGI PRAMUWISATA DI BALI - Ni Wayan Meidariani; Ni Luh Gede Meilantari (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Abstract. The there is a big need of labours in tourism, trour beaurues, and hotel sectors in Bali, particularly those who are able to speak Japanese due to the fact that many Japanese tourits are interested in visiting Bali. However, the most of current tourist guides who speak Japanese acquire their Japanese from non formal education, such as from reading books or listening materials they gain by themselves. This, in turn, effect on their performance which cannot be done maximally in their service to the Japanese toruists, particularly due to their lack of vocabulary building. This condition has stimulated for a research to be conducted which produces an outcome ina form of dictionary. The entry of the Japanese words were collected through direct observation in field when there were conversations between Japanese tourits and their guieds or tour leaders or information staff. This reseach is a continuation whose goal is to evaluate its acceptance and the evaluation is conducted by experts and people work on tourism sector. The research applied descriptive qualitative method. The reseach resulted in a development product of a Japanese dictionary draft. This draft was evaluated by people majoring the Japanese language and users of the dictionary,that is people running tourism sector. Questionairs were handed out to the toruist guides in Bali to collect their feedback on the dictionary and its role in increasing their vocabulary on tourism. The result shows that the dictionary is useful to enrich their vocabulary building. It can be read from the positive responses since 30% of the words in the dictionary cannot be understood their use in context. This means that the dictionary increases their knowledge of Japanee words of tourism. Key words: dictionary, vocabulary, tourism practionist, Japanese language